Pengaruh Pendidikan Kewirausahan, Efikasi Diri Dan Lingkungan Keluarga Terhadap Intensi Berwirausaha Mahasiswa Fakultas Ekonomi Universitas Negeri Jakarta - Diah Ayu Kumalasari; Henry Eryanto; Aditya Pratama (Peneliti.net, 2022)
This study aims to determine the direct and indirect effect of Entrepreneurship Education, Self-Efficacy and Family Environment on Entrepreneurial Intentions in Jakarta State University students. This study uses a quantitative approach. The independent variables of this research are Entrepreneurship Education and Family Environment. Self-efficacy as a moderating variable. While the Entrepreneurial Intention as the dependent variable uses Theory of Planned Behavior. The sample of this study consisted of 260 students of the Faculty of Economics, State University of Jakarta, class of 2018 and 2019. The sampling method used was proportional random sampling. The data collection technique of this research used a questionnaire. The instrument validity test uses Product Moment correlation, and the reliability test uses Cronbach's Alpha. Data analysis used path analysis with IBM SPSS Statistics 25. The results of this study indicate that Entrepreneurship Education has a direct effect on Entrepreneurial Intentions. Self-efficacy has no direct effect on Entrepreneurial Intentions. Family environment has a direct effect on Entrepreneurial Intentions. Self-efficacy is not able to moderate the indirect effect of Entrepreneurship Education and Family Environment on Entrepreneurial Intentions.